Bilateral Birdshot Retinochoroiditis and Retinal Astrocytoma - Sunil Mamtora; Yun Wong; Dugald Bell; Teresa Sandinha (Case Reports in Ophthalmological Medicine)
Background. This case highlights the importance of recognising multiple pathologies within the eye which may not necessarily be linked. Both birdshot retinochoroiditis and astrocytoma are rare conditions. The case underlines the need for early identification and treatment of birdshot retinochoroiditis with steroids and disease modifying drugs. Astrocytoma in the absence of tuberous sclerosis is also uncommon. Case Presentation. A 36-year-old male presented with 3-month history of bilateral progressive flashing lights and floaters. He was systemically well with no significant past medical history. Fundal examination revealed retinal vasculitis and active creamy lesions in the choroid radiating from the optic nerve. In the supranasal periphery of the right eye there was a raised white, jagged lesion protruding into the vitreous. Fluorescein angiogram and indocyanine green showed marked venous vasculitis, hypofluorescence, and disc leakage in keeping with birdshot retinochoroiditis. The supranasal lesion features were in keeping with astrocytoma and this was thought to be a coincidental finding. Conclusions. Retinal astrocytoma may be present as an isolated ocular finding; however, patients must still be investigated for tuberous sclerosis which is the most common association. Birdshot retinochoroiditis typically responds well to steroid therapy, and disease modifying drugs should be considered as soon as possible.